2020
DOI: 10.1002/cpp.2524
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Norwegian version of the Desire Thinking Questionnaire (DTQ): Associations with problem drinking, nicotine dependence and problematic social media use

Abstract: The aim of the current study was to test the validity of the Norwegian version of the Desire Thinking Questionnaire (DTQ). Three cross-sectional surveys were conducted investigating the psychometric properties of the DTQ in alcohol use (N = 588), nicotine use (N = 446) and social media use (N = 359). Principal components and confirmatory factor analyses supported the original two-factor solution consisting of verbal perseveration (VP) and imaginal prefiguration (IP); however, one item was removed to obtain goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…We theoretically propose and empirically embed a place for desire thinking within the I-PACE model [42,43] in the realm of internet-use disorders including gaming [26][27][28][29], pornography viewing [27,30], social networks use [20,27], shopping and gambling [27], and the general use of the internet [5, 7, 31•, 32, 33]. Evidence suggests a close link between desire thinking and aversive triggers, where desire thinking might be used as a maladaptive coping mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We theoretically propose and empirically embed a place for desire thinking within the I-PACE model [42,43] in the realm of internet-use disorders including gaming [26][27][28][29], pornography viewing [27,30], social networks use [20,27], shopping and gambling [27], and the general use of the internet [5, 7, 31•, 32, 33]. Evidence suggests a close link between desire thinking and aversive triggers, where desire thinking might be used as a maladaptive coping mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study gives a first impression that the temperamental constitution of seeking novel and exciting sensations seems to contribute to the mental simulation of experiences in order to experience gratification. The postulated relief-oriented pathway gathers two studies in the context of internet-use disorders that found mild bivariate correlations between desire thinking and psychological distress (e.g., depressive symptoms) among individuals playing internet games [26] and individuals using social networks problematically [20], indicative of a relation that cannot be interpreted causally. However, an investigation of desire thinking within a structural equation model revealed the idea that desire thinking may be used to alleviate negative mood states in the context of potentially addictive online activities [27].…”
Section: Processing Of Triggers and Desire Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PHQ-4 has also demonstrated good reliability and validity in clinical and population samples for the Norwegian and German versions (e.g. [ 47 50 , 53 , 54 ]). McDonald’s omegas in this study were .91 (Norwegian sample), and .91 (German-speaking sample).…”
Section: Methodsmentioning
confidence: 99%
“…The PHQ-4 has demonstrated good reliability and validity in clinical and population samples for the Norwegian and German versions [e.g. [44][45][46][47][48][49]. Cronbach's alphas in this study were .82 (Norwegian sample), and .84 (German-speaking sample).…”
Section: General Mental Distressmentioning
confidence: 62%